EFEKTIFITAS DAN DAMPAK PELAKSANAAN PROGRAM BEASISWA PENDIDIKAN MISKIN DAN BERPRESTASI (BIDIK SIMISI) TERHADAP ANGKA PUTUS SEKOLAH DAN ANGKA PARTISIPASI MURNI DI PROVINSI BALI - primadewi, putu pendit; sribudhi, made kembar; marhaeni, A.A.I Ngurah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Efforts to achieve the targets set together other world  countries  in the Millennium Development Goals (MDG's) is a noble task that is being carried out by the Bali Provincial Government. Bali Provincial Government in its efforts to achieve its targets has been putting  efforts to accelerate the achievement of the Millennium Development Goals (MDGsBreakthrough has been done by the Bali Provincial Government through the Department of Education, Youth and Sports within Education Program Costs for Poor Students Academic Achievement in the Field (BIDIK SIMISI). BIDIK SIMISI program aims to encourage economically deprired students to reach academic achievement by getting into education Vocational School (SMK). The evaluation is then very important to measure the extent of the effectiveness of programs  implemented in line with the expectations. This study aims to analyze the effectiveness and impact of the implementation of the Poor and Achievement Scholarship Program (BIDIK SIMISI) in the relation  to Dropout Rate and Pure Participation Rate in Bali Province. To achieve these objectives the research is being conducted in SMKN I Denpasar. The  primary data was collected by descriptive quantitative for the questionnaire  , qualitative data (secondary) colleted by interview, observation, and documentation was analyzed by qualitative analysis. The results showed that ; 1) The level of effectiveness of the program in term of inputs, processes and outputs was relatively effective, 2) Implementation of the poor and achievement schlarship program did not negatively impact the school dropout rate, 3) Implementation and achievement scholarship program had a poor negative impact on net enrollment in Bali province the first year of implementation, while the second and third year had a positive impact on net enrollment.
Keywords: Poor Scholarship and Achievement, Dropout Rate, Pure Participation Rate